Career in the narratives of early adolescents - Piorunek, Magdalena (Kultura-Społeczeństwo-Edukacja, 2019)
IIn the paper “Career in the narratives of early adolescents” I set out to describe the selected aspects of constructing an identity during adolescence in the context of prospective professional development among young individuals, who seek to define their future selves. The paper also outlines the social and cultural context of constructing a career, which should potentially be addressed by young individuals long before they enter the labour market. The paper also describes the selected findings of my own concerning career narratives constructed by early adolescents, descriptions of selected career aspects provided by middle school students, and their personal predictions and plans on their prospective life as professionals.